Morphological Characterization of Cauliflower Varieties/Cultivars using DUS Characters - Singh, B; Chaubey, T; Jhan, Aastik; Upadhyay, DK; Pandey, SD (SAARC Journal of Agriculture, 2014)
No Abstract Available DOI: http://dx.doi.org/10.3329/sja.v11i2.18413 SAARC J. Agri., 11(2): 182-191 (2013)